PENGUATAN KOHESI SOSIAL MELALUI EDUKASI ANTI-BULLYING PADA SISWA SEKOLAH DASAR MIN 2 AMBON - Johan Bruiyf Bension; Ammar Muhammad Heluth; Dame K. Situmorang; Laura Bianca Huwae; Stazia Noija (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Bullying remains a prevalent social issue within elementary school environments and may adversely affect students’ psychological development, social relationships, and learning processes. Such conditions have the potential to weaken social cohesion among students and hinder the establishment of a safe and inclusive school environment. Based on preliminary observations conducted at MIN 2 Ambon, bullying behaviors in the form of mockery, verbal humiliation, and minor physical aggression were still identified among students. This community service activity aimed to strengthen students’ social cohesion through anti-bullying education while enhancing their understanding of the negative impacts of bullying on individuals and the social environment. The program was conducted on October 25, 2025, involving 22 students from grades IV–VI, teachers, and the school principal. The implementation methods included preliminary observation, educational socialization, interactive lectures, group discussions, question-and-answer sessions, demonstrations of bullying behaviors, and participatory evaluation. Educational materials were delivered using PowerPoint presentations and instructional videos to enhance participant engagement and comprehension. The results demonstrated an improvement in students’ understanding of the importance of respecting peers, fostering empathy, and maintaining positive social relationships within the school environment. Furthermore, students showed active participation throughout the activity and were able to identify bullying behaviors along with appropriate preventive measures. Support from the school administration also contributed significantly to the success of the program in creating a safer, more interactive, and conducive learning atmosphere. In conclusion, anti-bullying education may serve as an effective strategy for strengthening social cohesion and promoting an inclusive school culture among elementary school students.